ANALYSIS OF FIGURATIVE LANGUAGE IN THE NOVEL THE KITE RUNNER - Amir, Rini; Adam, Samsudin Hi.; Supriyadi, Agus (Universitas Khairun, 2024)
The purpose of this research is to find out and analyze the types of figurative language and its meaning in the novel